The influence of C/Ta ratio on TaC precipitates in Co-Re base alloys investigated by small-angle neutron scattering. (15th June 2017) - Karge, L.; Gilles, R.; Mukherji, D.; Strunz, P.; Beran, P.; Hofmann, M.; Gavilano, J.; Keiderling, U.; Dolotko, O.; Kriele, A.; Neubert, A.; Rösler, J.; et al.
Abstract: Co-Re alloys are being developed to supplement Ni-base superalloys in future gas turbines for ultra-high temperature applications. The finely distributed mono-carbide phase of TaC is an important strengthening phase in this alloy, and interacts with dislocations during high temperature creep deformation. This study aims to determine and to understand the volume fraction and size distribution of TaC precipitates in dependence of C/Ta stoichiometry and heat treatment by means of in-situ small-angle neutron scattering. At measuring temperatures of 1173 K, 1373 K and 1473 K, a stable population of fine TaC <100 nm size is formed during ageing for a wide range of C/Ta stoichiometry but with considerably different volume fraction and coarsening behavior. Important parameters for mechanical properties of the material, such as particle size distribution and inter-particle distance, were determined. It is shown that the phase transformation from γ-matrix (fcc) ↔ ε-matrix (hcp) of the Co-Re matrix has a considerable influence on the TaC precipitate formation. Graphical abstract: Image 1